Sherlock Holmes and the telegram from hell : [large type] extracts from the diaries of John H. Watson, M.D. June 1916-November 1918 - Meyer, Nicholas, 1945- (Thorndike Press large print mystery series., 2025)
"June 1916. With a world war raging, John H. Watson, M.D. is operating on the wounded when his labors are interrupted by Sherlock Holmes, with a black eye, a missing tooth, and a cracked rib. In pursuit of a coded telegram sent from Berlin to an unknown recipient in Mexico, Holmes and Watson must cross the Atlantic, dodge German U-boats and assassination attempts, and evade the intrigues of young J. Edgar Hoover, while enlisting the help of a Washington socialite as they seek to foil the schemes of Holmes's nemesis, German spymaster Von Bork"--